Peningkatan Mutu Pendidikan HomeschoolingKak Seto Solo Pada Satuan Sma DanKualitas Lulusannya - Cahyanti, Novi, Prof. Dr. Harsono, SU (2016)
The general purpose of this research is to describe the characteristics the good of Homeschooling and the purposes thus research specifically to describe the characteristics of a good teacher in Homeschooling Kak Seto Solo, describe the characteristics of students who good in Homeschooling Kak Seto Solo, describing the learning interaction between the teacher and the learners in Homeschooling Kak Seto Solo, and to know the graduates the Homeschooling Kak Seto Solo accepted at a good college. Qualitative research with the ethnographic research design. Resource is the principal, tutors, and students of Homeschooling. Data collection techniques used interview, observation, and documentation. Technique authenticity of data triangulation technique. The techniques date analysis is in the site. The conclusion that can be drawn from this study are: 1) Characteristics of good teachers in Homeschooling Kak Seto Solo is to understand his role as a teacher and friend to the students, to understand the needs of each student, patient, achieving 2) Characteristics of a good student in Homeschooling Kak Seto Solo has life skill that is good, has a planning after graduate from Homeschooling Kak Seto Solo, have solidarity between fellow friends, although it has limitations in the physically but has the spirit in learning 3) the learning interaction of the teacher and the students in Homeschooling Kak Seto Solo the tutor use the methods interesting learning, students are active in the activities of learning, tutor present the material clearly, tutors give attention to the students who have a deficiency 4) Graduate from Homeschooling Kak Seto Solo went on to college like in the UNS, UGM, Diponegoro University, Semarang University, UMS, went on a school abroad, and there are continuing the family business.